2021
DOI: 10.1016/j.ejvs.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – External Applicability of the COMPASS and VOYAGER-PAD Trials on Patients with Symptomatic Lower Extremity Artery Disease in France: The COPART Registry

Abstract: WHAT THIS PAPER ADDS Only 30.1% of patients hospitalised for symptomatic lower extremity artery disease are eligible for rivaroxaban 2.5 mg twice daily plus aspirin, based on the COMPASS or VOYAGER-PAD criteria. These patients have higher rates of ischaemic events than those in these trials. The one year cumulative incidences were 6.0% (95% confidence interval [CI] 4.3 e 8.1) in the COMPASS eligible subset vs. 3.5% (95% CI 2.9 e 4.3) in the COMPASS control arm for major adverse cardiovascular events, and 27.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Network meta-analysis of individuals with PAD from CAPRIE and COMPASS demonstrated no superiority of rivaroxaban and aspirin over clopidogrel [ 39 ]. Furthermore, both COMPASS and VOYAGER excluded patients with significant multi-morbidity and those considered at high risk of bleeding and, based on registry data, only 30% of patients hospitalised with symptomatic PAD would have been eligible for inclusion [ 40 ].…”
Section: Medical Management Of Padmentioning
confidence: 99%
See 1 more Smart Citation
“…Network meta-analysis of individuals with PAD from CAPRIE and COMPASS demonstrated no superiority of rivaroxaban and aspirin over clopidogrel [ 39 ]. Furthermore, both COMPASS and VOYAGER excluded patients with significant multi-morbidity and those considered at high risk of bleeding and, based on registry data, only 30% of patients hospitalised with symptomatic PAD would have been eligible for inclusion [ 40 ].…”
Section: Medical Management Of Padmentioning
confidence: 99%
“…Furthermore, many patients with symptomatic PAD also have indications for long-term anticoagulation (e.g. those with atrial fibrillation) in whom the added benefit of antiplatelet therapy is unknown and is likely to significantly increase bleeding risk [ 40 ].…”
Section: Medical Management Of Padmentioning
confidence: 99%
“…Lapébie et al reported on the external applicability of both COMPASS and VOYAGER to patients in the French COPART registry, finding that only 30.1% of patients would have been eligible for inclusion in either trial. 4 In this issue of the Journal, Søgaard et al present a similar analysis of patients in the Danish Vascular Registry, finding 27.1% of patients would have been eligible. 5 Both studies found that patients in the registries (both eligible and ineligible for the trials) were at higher risk of major ischaemic events than those in the control arms of the trials, making it conceivable that dual pathway inhibition might be even more beneficial than the results of the trials would suggest.…”
mentioning
confidence: 97%
“…Trial subgroup analysis and 'real world' application of trial results shine a harsh spotlight on these issues. 4,5 The allimportant risk balance is then debated extensively by clinicians trying to do the right thing for an individual patient.…”
mentioning
confidence: 99%
“…Recently, 2 studies based on French and Danish registry data have provided data on the external applicability of VOYAGER-PAD to patients encountered in routine clinical practice. 9,10 In both studies, fewer than one-third of patients who underwent revascularization in routine practice would have been eligible in the VOYAGER-PAD trial. Compared with participants enrolled in VOYAGER-PAD, patients in routine care were older and had more severe PAD, higher bleeding risk, and generally poorer prognosis.…”
mentioning
confidence: 99%